Silencing Universities by Stealth: An Invisible Consequence of our University Crisis - Death, Russell; Joy, Mike (New Zealand Science Review, 2024)
Independent, well-informed experts from academia largely serve as bastions of evidence-based social and scientific commentary, ensuring integrity and accuracy amidst the deluge of false narratives. However, although it is enshrined in the legislature that universities should act as a critic and conscience of Aotearoa New Zealand, this role provides limited financial benefits to the university's bottom line. As financial drivers have become more influential in determining what is taught and how staff spend their time, this public good, which has always been on the periphery of staff tasks, is slowly disappearing. As an example, academics at Massey University have previously been active and vocal researchers, educators, and critics of the state of freshwater in Aotearoa New Zealand. However, Professor Russell Death and Dr Mike Joy, who have led the freshwater ecology team, have now both been pressured to leave, so in 2024, Massey University will no longer teach any courses in freshwater ecology. Neither of us was made redundant or directly asked to leave, but the constantly shifting teaching pressures and altered managerial priorities have left us both at Massey without time and/or support to continue our community outreach and public engagement. We will provide examples of the difficulty of being a critic and conscience at a university where the financial bottom line is the key imperative. Unfortunately, the dwindling number of freshwater ecology graduates being trained and the lack of critical commentary on Aotearoa New Zealand's freshwater crisis may go largely unnoticed. We believe the current university crisis will exacerbate the loss of this essential public good, with few people even aware of what has been lost.